Application of Problem Based Learing Model in Analyzing Nationalism of Poetry "Di Bawah Layar" by D. Zawawi Imron - Yusuf Sulaeman (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2018)
Effectiveness of learning, interest in literary appreciation and the student's ability to analyze the elements of nationalism, theme and mandate of poetry on the ground remains low. Based on that writing is restricted to three things, increase the effectiveness of learning, improve the ability of students to apply learning model of problem based learning to learning to analyze the elements of nationalism, theme and mandate poetry class X SMK Al-Ibrohimiyah Cianjur. The method used in this study, classroom action research cycle test techniques, observation sheets and questionnaires. Research conducted three cycles. The results of the study managed to increase; (1) The effectiveness of learning increases, the first cycle is still rowdy class, then the second cycle has begun not rowdy, and the third cycle has been conducive; (2) The interest of students to appreciate literature increased, in the first cycle students are active for only a small sebagin, on the second cycle by almost half and the third cycle to a great extent; (3) The ability of students to analyze the elements of nationalism, theme and mandate of poetry increased, in the first cycle students' average score of 66.19 in cycle II reached 75.95 and the third cycle reached 91.66. It was concluded that the application of the teaching model of problem based learning to learning to analyze the theme and mandate puiisi class X SMK Al-Ibrohimiyah Cianjur can improve the effectiveness, student interest and student learning outcomes. Keywords:  problem based learning, nationalism, structural and poetry.